Implementation of Principal Academic Supervision to Improve the Pedagogical Competence of Elementary School Teachers - Windriati; Senowarsito; Maryanto (Jurnal Penelitian Pendidikan IPA, 2025)
Academic supervision is an important factor in ongoing professional development efforts to improve the quality of learning. This study aims to describe the implementation of academic supervision by the principal in improving the pedagogical competence of teachers at SD Negeri 06 Tegalsari, Pemalang Regency. The study used a descriptive qualitative approach with the principal, class teachers, and subject as teachers as subjects. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results show that academic supervision is implemented through three stages: planning, implementation, and evaluation and follow-up. In the planning stage, the principal collaboratively involves teachers in developing objectives, schedules, and supervision instruments. Supervision is carried out in a humanistic and reflective manner, emphasizing dialogue and professional mentoring, rather than merely administrative supervision. Evaluation is carried out through joint reflection and follow-up in the form of ongoing coaching that encourages teachers to improve learning practices. The implementation of academic supervision has been proven to improve teachers' pedagogical competence in designing teaching materials, selecting appropriate learning strategies, and conducting meaningful learning evaluations. Thus, planned, collaborative, and reflective academic supervision can be a strategic instrument in developing teacher professionalism and improving the quality of education in elementary schools.